Filosofi Circular Economy Sebagai Refleksi Etis Antara Pertumbuhan Ekonomi dan Kebijaksanaan Ekologis - Misdawita; Hasnah Faizah (JURNAL ARMADA PENDIDIKAN, 2025)
The circular economy has emerged as an alternative solution to the linear economic model that focuses on unsustainable resource consumption and waste generation. In the global context facing an environmental crisis, this concept offers a more sustainable approach by prioritizing efficient resource use, material recovery, and waste reduction. This article examines the philosophy of the circular economy as an ethical reflection that balances economic growth with ecological wisdom. Through an in-depth literature review, the article highlights the evolution of the circular economy concept, the challenges of its implementation, and the social and ethical dimensions that must be considered to achieve the goals of the circular economy in a just and inclusive manner. The philosophy behind the circular economy invites us to reflect on the linear economic growth paradigm that has dominated the global production and consumption system, which in reality often contributes to severe environmental degradation. This research reveals that while the circular economy offers great potential for achieving efficiency and sustainability, its implementation requires serious attention to aspects of ethics, social justice, and intergenerational responsibility. In this context, this article aims to delve deeper into how circular economy principles can be integrated with ecological policies that respect planetary limitations and human well-being, and to provide guidance for the development of more sustainable and equitable policies in the future.